Kesesuaian Tingkat Harapan Dan Tingkat Kepuasan Masyarakat Terhadap Sarana Dan Prasarana Di Perumnas Tlogosari Kota Semarang - Muhammad Fikri Rusdiyanto; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2018)
Perumnas Tlogosari Semarang is one of the residential area units planned by Perum Perumnas (Public Housing Company) Branch V as the provision of urban housing for middle to low-income residents. The purpose of housing development is the implementation of housing in accordance with it’s function for improving welfare. In fact, there are several quality problems, such as housing feasibility, environmental health, dense residential space, and quantity problems such as the growing gap between rapid population growth and the provision of new or substitute housing. Typically, the housing problem focuses on the lack of suitable housing unit. In reality, what should be the problem is the lack of a housing unit which has a value that suitable for its occupants and suitable with the expectation of its occupants. Based on the background above, the researcher tried to research to find out how much the results obtained by the community toward initial expectations of the community and their usefulness, how was the result of the availability of facilities and infrastructure of Perumnas Tlogosari. The research method that used is a quantitative method. Data collection methods include document review, observation, interview, and questionnaire. Analysis methods used are descriptive statistic analysis, scoring analysis, and importance performance analysis. Analysis results show that the level of expectation according to the community for the availability of facilities and infrastructure in Perumnas Tlogosari is good and the level of satisfaction according to the community for the availability off acilities and infrastructure in Perumnas Tlogosari is satisfied. Analysis results also provide information that over all thepriority off acilities that must be repaired fromt he developer is the access of non-residential community roads and clean waters upply facilities/PDAM. Then, the distance of the housing location to education facilities, waste water facilities, housing creates a comfort and cool atmosphere, housing has a good absorption capacity, mutualism symbiosis between the non-housing and housing communities, the width, and condition of the main road, worship facilities, plumbing or piping systems, solid waste facilities, and electricity facilities are expected to be appropriately maintained by the developer.